2020
DOI: 10.1029/2019ms001896
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Stochastic Parameterization: Generative Adversarial Networks in the Lorenz '96 Model

Abstract: Stochastic parameterizations account for uncertainty in the representation of unresolved subgrid processes by sampling from the distribution of possible subgrid forcings. Some existing stochastic parameterizations utilize data‐driven approaches to characterize uncertainty, but these approaches require significant structural assumptions that can limit their scalability. Machine learning models, including neural networks, are able to represent a wide range of distributions and build optimized mappings between a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 88 publications
(120 reference statements)
1
122
0
Order By: Relevance
“…Furthermore, for some poorly understood processes for which observational data are available (e.g., clouds), data-driven surrogate models built using such data might potentially outperform physics-based surrogate models [22,30]. Recent studies have shown promising results in using AI to build data-driven parameterizations for modeling of some atmospheric and oceanic processes [33,34,35,36,37,38,39,40]. In the turbulence and dynamical systems communities, similarly encouraging outcomes have been reported [41,42,43,44,45,46,26,47,48,49] .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, for some poorly understood processes for which observational data are available (e.g., clouds), data-driven surrogate models built using such data might potentially outperform physics-based surrogate models [22,30]. Recent studies have shown promising results in using AI to build data-driven parameterizations for modeling of some atmospheric and oceanic processes [33,34,35,36,37,38,39,40]. In the turbulence and dynamical systems communities, similarly encouraging outcomes have been reported [41,42,43,44,45,46,26,47,48,49] .…”
Section: Introductionmentioning
confidence: 90%
“…As seen in Figure 5(A), RC-ESN accurately predicts the time series for over 2.3 MTU, which is equivalent to 460∆t and over 10. 35 Lyapunov timescales. Closer examination shows that the RC-RSN prediction follows the true trajectory well even up to ≈ 4 MTU.…”
Section: Short-term Prediction: Comparison Of the Rc-esn Ann And Rnmentioning
confidence: 99%
“…In our study we trained a deep neural network to emulate the CRM tendencies. The offline validation scores were very encouraging (Gentine et al, 2018) even though the deterministic ML parameterization was unable to reproduce the variability in the boundary layer. When we subse-quently implemented the ML parameterization in the climate model and ran it prognostically (online), we managed to engineer a stable model that produced results close to the original SP-GCM.…”
Section: Rasp Et Al (2018) -Super-parameterization With a Neural Netmentioning
confidence: 98%
“…As a result, to make the simulations feasible, a few strategies have been developed, which mainly involve only solving for slow/large-scale variables and accounting for the fast/small-scale processes through surrogate models. In weather and climate models, for example, semiempirical physics-based parameterizations are often used to represent the effects of processes such as gravity waves and moist convection in the atmosphere or submesoscale eddies in the ocean (Stevens and Bony, 2013;Hourdin et al, 2017;Garcia et al, 2017;Jeevanjee et al, 2017;Schneider et al, 2017b;Chattopadhyay et al, 2020b, a). A more advanced approach is "super-parameterization" which, for example, involves solving the PDEs of moist convection on a high-resolution grid inside each grid point of large-scale atmospheric circulation for which the governing PDEs (the Navier-Stokes equations) are solved on a coarse grid (Khairoutdinov and Randall, 2001).…”
Section: Introductionmentioning
confidence: 99%